Dynamic characteristics analysis of high speed rotating thin film antenna - Yao Feng; Jimei Wu; Mingyue Shao (Results in Physics, 2022)
The thin-film antenna is in a state of high-speed rotation in space, and studying the influence of its structure size on its vibration characteristics can avoid the occurrence of resonance. The rotational vibration characteristics of thin film antenna are studied by using the Absolute Nodal Coordinate Formulation (ANCF) with improved computational efficiency. The triangular element is used to mesh the thin film antenna, the kinetic energy, strain energy and external force potential energy of the element are calculated. The mass matrix and stiffness matrix of the element are transformed into the overall mass matrix and stiffness matrix through Boolean matrix. According to the rotation equivalent model, the centrifugal force potential energy generated by the high-speed rotation of the thin film antenna is transformed into the centrifugal force stiffness matrix. The relationship between rotational speed and natural frequency of thin film antenna under different structural sizes is analyzed. By analyzing the critical speed generated by the front traveling wave and the back traveling wave, the theoretical basis for the structural design of thin film antenna is improved.